PERENCANAAN PENGEMBANGAN MODAL MENGUNAKAN AKUN REGULER PERDAGANGAN BERJANGKA DI PT. AGRODANA FUTURES BANDUNG - panji, panji; Supriyoso, Patria (JEBIM Prima, 2024)
Dynamic changes in the business world mean that business people, both beginners and those who have been in business for a long time, do not dampen their desire to continue to expand, open or increase income from their businesses.One business opportunity that is simple, practical and does not require too much infrastructure to start is online trading or futures trading. Apart from providing profit growth on capital, trading opens up opportunities for anyone to earn income without being tied to the company where they work and can be done independently, thereby creating new jobs for the Indonesian people. The aim of this research is to analyze how capital develops using a regular futures trading account at PT. Agrodana Futures Bandung. The method used by the author is qualitative by conducting interviews with trading players, especially those who have been doing it for more than 3 years, how they manage and develop their trading business so that their initial capital continues to grow significantly in a short period of time. The conclusion of this research is that online trading is one of the best alternatives for anyone who is a business actor in growing capital, developing a business or other business goals and its progress continues to increase from time to time. The author feels that this research will have a positive impact on anyone who wants to continuously increase their economic income through online trading